EFEKTIVITAS PIJAT BAYI TERHADAP PENINGKATAN KOORDINASI MOTORIK PADA BAYI USIA 6-12 BULAN DI WILAYAH PUSKESMAS PULAU GADANG KABUPATEN KAMPAR - Nasraini, Nasraini; Nadia, Fatma; Mardiya, Rizka; Fitria, Nurhidaya (Ensiklopedia of Journal, 2025)
Motor coordination in infants is a crucial aspect of growth and development in early childhood. One form of stimulation that can support this development is infant massage. This study aims to determine the effectiveness of infant massage on improving motor coordination in infants aged 6–12 months in the working area of Pulau Gadang Public Health Center, Kampar Regency. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 18 infants selected through total sampling. The research was conducted in April-May 2025. The intervention consisted of daily infant massage administered once a day for 8 consecutive days. Motor coordination was assessed using the Developmental Pre-Screening Questionnaire (KPSP) before and after the intervention. The results showed that the average motor coordination score increased from 8.33 before the intervention to 9.44 after the intervention. Based on the Wilcoxon statistical test, a p-value of < 0.05 was obtained, indicating a significant difference in motor coordination before and after infant massage. Thus, infant massage was proven effective in enhancing motor coordination in infants aged 6–12 months. This study provides important implications for healthcare workers and parents to implement infant massage as part of early childhood developmental stimulation. Moreover, these findings can serve as a reference for developing child growth and development intervention programs at the primary healthcare level.Keywords: Infant massage, motor skill coordination, KPSP